Lactation care by nurse consultants: It just hit me, there's a field there (Revista Contexto & Saúde, 2025)
The objective of this study is to describe lactation care through consulting provided by nurses. This is an exploratory-descriptive study with a qualitative approach. Twenty lactation consultant nurses participated. Semi-structured interviews were conducted via Google Meet, recorded and transcribed. The data were analyzed in the thematic modality. Lactation consulting arises from personal experiences and the desire to undertake in this area. However, the topics of breastfeeding and entrepreneurship are superficial in nursing training for qualified practice. It is provided in online and in-person modalities, occurring mainly in the puerperium and at the clients' homes. As it is aimed at mother-baby-family and the extended network if possible, its actions include general guidance, baby care and clinical management in lactation. Consulting promotes maternal empowerment and self-confidence to breastfeed, allows for autonomous work by the nurses, but also involves overload, lack of a fixed salary and demand for successful breastfeeding outcomes. We conclude that lactation consultancy is an emerging entrepreneurial professional field in nursing. The expansion of this powerful strategy in public and private health services may contribute to increasing breastfeeding rates. The role of the nurse consultants favors best practices in lactation that positively imply the promotion, protection and support of breastfeeding and child health.